IMPLEMENTING SCIENTIFIC RESEARCH INTO PRACTICE: PROBLEMS, INNOVATIVE MECHANISMS AND SYSTEMATIC SOLUTIONS (Universal International Scientific Journal, 2026)
This article analyzes the theoretical foundations of implementing scientific researchresults into practice, existing institutional challenges, and innovative mechanisms for overcomingthem. Based on the experience of Uzbekistan and international scientific approaches, the relevance ofthe “science – industry – government” integration is substantiated. The study develops systematicproposals relying on legal and regulatory documents, academic sources, and modern innovationmodels.
Keywords: scientific research; innovation; commercialization